Indian champions : profiles of famous Indian sportspersons - Garg, Chitra 1954- (Delhi : Rajpal, 2010)
Short biography of eminent Indian sports persons
Keywords: Athletes -- India -- Biography; Sports -- India -- Biography; Champions (Game)